Respuesta :

So, we have the equation

3x²-4x = 20

Which can be rewritten as:

3x²-4x-20 = 0

a= 3

b= -4

c= -20 (incorrect in the original version, that said it was 20)

[tex]\begin{gathered} x=\frac{-b\pm\sqrt{b2-4ac}}{2a} \\ CORRECT \end{gathered}[/tex]

I'm writing the correct version of the next step of the quadratic equation below. The original is INCORRECT.

[tex]x=\frac{-(-4)\pm\sqrt{(-4)²-4(3)(-20)}}{2(3)}[/tex][tex]x=\frac{4\pm\sqrt{16+240}}{6}[/tex][tex]\begin{gathered} x=\frac{4\pm\sqrt{256}}{6} \\ x=\frac{4\pm16}{6} \\ x=20/6 \\ x=-2 \end{gathered}[/tex]